Development of a Model for optimum saturation efficiency of an evaporative cooling system - Dzivama, A. U.; Igbeka, J. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
The performance efficiency of an evaporative cooling system (fan and pad) under varied levels of parameters (water flow rate, pad thickness and air velocity) was evaluated using a 3-factor statistical design. A response equation was developed and was used to obtain the optimum levels of the parameters required for optimal operation of the evaporative cooling system. Simulation result of the response equation indicated that for optimum operation of the evaporative cooling system, a water flow rate of 4.4L/min, pad thickness of 47mm and air velocity of 1.6m/s was required. Simulated saturation efficiency of 70.4 % was obtained with these values while the measured was 84.6 % at water flow rate of 4.5L/min, pad thickness of 60mm and air velocity of 2.3m/s.